The Role of Quality of Life, Life Satisfaction, Feelings of Loneliness, and Adaptability to Purpose in Life Adults in Disaster-Prone Areas of Earthquakes - Eriyono Budi Wijoyo; Mustikasari (Universitas STRADA Indonesia, 2025)
Background: Young people often face challenges in determining their life goals due to various influencing factors. This issue is a major problem for young people living in earthquake-prone areas. Purpose: This study aims to develop and test a structural equation model (Structural Equation Modeling/SEM) of life goals in young adults in areas prone to earthquake disasters. Methods: The model used in this study is SEM (Structural Equation Modeling) which is operated through the Smart PLS program. SEM data processing builds a measurement model and a structural model. The SEM process involved three key steps: confirmatory factor analysis to test the instrument's validity and reliability, path analysis to evaluate the relationships between variables, and structural model analysis to assess and predict the model's overall suitability. Results: Most of the study participants were female (87.2%) aged 18-21 years (67.5%). More than half of the respondents were undergraduate students (68.9%) who were single (96.5%), and respondents who had no history of trauma (66.1%). Normality analysis showed that the absolute values ​​of skewness and kurtosis of all variables did not exceed 1.97 and 2.58, respectively, thus meeting the recommended criteria for a normal distribution. In this study, the fit index of the hypothesized model met the recommended criteria so that the overall model fit was considered acceptable. This indicates that the hypothesized life purpose model for young adults in areas prone to earthquake disasters is appropriate. Path analysis showed that 10 of the 15 paths were statistically significant. Conclusion: Model development shows variables that are quite effective in forming a model to improve the life purpose of young adults in areas prone to earthquake disasters.